ANTIMICROBIAL ACTIVITY OF ESSENTIAL OILS OF XYLOPIA AETHIOPICA - Fleischer, Theophilus Christian; Mensah, Merlin Lincoln Kwao; Mensah, Abraham Yeboah; Komlaga, Gustav; Gbedema, Stephen Yao; skaltsa, Helen (African Journal of Traditional, Complementary and Alternative Medicines, 2008)
Xylopia aethiopica is a medicinal plant of great repute in West Africa which produces a variety of complex chemical compounds. The fresh and dried fruits, leaf, stem bark and root bark essential oils showed various degrees of activity against the Gram positive bacteria, Bacillus subtilis and Staphylococcus aureus, the Gram negative bacteria Pseudomonas aeruginosa and the yeast-like fungus Candida albicans, using the cup plate method,. However, none of the oils showed activity against Escherichia coli.